Elsayed A Usage and Knowledge of the Over- the- Counter Medicines Among Patient Visiting Ophthalmic Hospital in Wad Medani, Sudan - ELSAYED, AMANI M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective The aim of this work is to determine the usage pattern and knowledge of OTC medicines among Sudanese attending Ophthalmic hospital in Wad-Medani/Sudan. Methods It is a cross-sectional study in which 500 patients were surveyed. Results Participants had taken OTC medicines to treat headache, pain, allergy, heart pain, etc. General knowledge of participants is poor. Majority of respondents admitted having no knowledge about the active ingredient, the maximum dose or side effects of paracetamol. One-third of respondents had taken a dose lower or higher than the recommended one. The main reason of taking larger dose was the intensive pain. More than a half (59.0%) of respondent reported using more than one OTC medications when they had multiple symptoms. The results showed that knowledge is associated with the level of education. Regarding the sources of information, two third of respondents (68.8) get information about the non-prescription medicine from the pharmacist. Only 10.4% read information about the OTC medicines from the leaflet in the package. Conclusions In Sudan, pharmacists play major role in OTC medication safety as the illiteracy comprises high percentage.